The shape of the radio wavefront of extensive air showers as measured with LOFAR - Corstanje, A.; Schellart, P.; Nelles, Anna; Buitink, S.; Enriquez, J. E.; Falcke, H.; Frieswijk, W.; Hörandel, Jörg R.; Krause, M.; Rachen, J. P.; Scholten, O.; Ter Veen, S.; et al. (Astroparticle Physics, 2015)
Extensive air showers, induced by high energy cosmic rays impinging on the Earth's atmosphere, produce radio emission that is measured with the LOFAR radio telescope. As the emission comes from a finite distance of a few kilometers, the incident wavefront is non-planar. A spherical, conical or hyperbolic shape of the wavefront has been proposed, but measurements of individual air showers have been inconclusive so far. For a selected high-quality sample of 161 measured extensive air showers, we have reconstructed the wavefront by measuring pulse arrival times to sub-nanosecond precision in 200 to 350 individual antennas. For each measured air shower, we have fitted a conical, spherical, and hyperboloid shape to the arrival times. The fit quality and a likelihood analysis show that a hyperboloid is the best parameterization. Using a non-planar wavefront shape gives an improved angular resolution, when reconstructing the shower arrival direction. Furthermore, a dependence of the wavefront shape on the shower geometry can be seen. This suggests that it will be possible to use a wavefront shape analysis to get an additional handle on the atmospheric depth of the shower maximum, which is sensitive to the mass of the primary particle. © 2014 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Cosmic rays; Extensive air showers; Radio emission; Wavefront shape